EVALUATION OF THE INCLUSION PROGRAM AT THE INCLUSIVE SENIOR HIGH SCHOOLS IN BOGOR, WEST JAVA: Empirical Study using the Context, Input, Process, and Product (CIPP) Method - Nixon; Prof. Dr. Bibin Rubini; Dr. Widodo Sunaryo (JF Publisher, 2023)
Education for children with special needs needs to be planned, implemented, monitored and evaluated based on quality standards. Therefore, it is required a successful strategy of providing learning and tutorials to develop progress in autistic children. The purpose of this evaluation research is to describe the results of an assessment of the inclusion program at Inclusive Senior High Schools in Bogor in order to improve and develop the inclusion program which has been implemented since 2010. Method of this research is qualitative with descriptive research type uses the Context, Input, Process, and Product (CIPP) method. Informants were determined using a purposive sampling technique in this study, who were Educators at Inclusive High Schools in Bogor Regency. While data collection techniques are carried out by observation, in-depth interviews with informants, and the use of written documents. Then to ensure the validity of the data in this study a triangulation technique was used. Furthermore, data analysis technique is using data reduction, data presentation and conclusion making. The results obtained from this research indicated that the process of implementing the Inclusion Program at Inclusive Senior High Schools in Bogor, West Java, has been implemented based on good procedures. This is because of the four effectiveness indicators indicate that the program is implementing well in the context, input, and process components, while in the product component the average is